DIPLOMASI PERTAHANAN INDONESIA DALAM MENCAPAI KESEPAKATAN SEGMEN C500-C600 DAN SUNGAI SIMANTIPAL DENGAN MALAYSIA - Alfian Wanadi; Yusnarida Eka Nizmi (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
This research discuss about defence diplomacy which Indonesian Government use in order to reach an agreement in C.500-C.600 Segment and Simantipal River. In this research, author focuses on policital aspect and national security especially in those segment. This territorial dispute problem between Indonesia and Malaysia marked by demarcation efforts that have been carried out since 1975. In order to analyze the problem, the researcher uses Boundary Making Theory and nation-state level analysis. The research method used by the researcher is a qualitative research method and the data obtained through books, journals, reports and newspapers. The results of this study indicate that Indonesia and Malaysia has reached an agreement in determining the boundaries of the terrirory especially in C.500-C.600 Segment and Simantipal River. It means that Indonesia have successfully carried out bilateral diplomacy. The bilateral diplomacy is carried out through forums helds between Indonesia and Malaysia, named Joint Indonesia-Malaysia Boundary Committee (JIM). Keywords: Border Line, Memorandum of Understanding, Diplomacy